Kesiapan Kompetensi Pelaku Jasa Konstruksi dalam Menghadapi e-Procurement di Wilayah Terpencil - Soltan Takdir; Girinius Wenda; Fera Auliyati (Rashid : Journal of Economic, 2025)
This study analyzes the readiness level of construction service companies in Jayawijaya Regency to implement e-Procurement. A quantitative descriptive method was used, focusing on three key indicators: knowledge, skills, and attitude. The results show that the overall readiness level is categorized as "Ready but needs improvement". While most respondents demonstrated a positive attitude toward e-Procurement, many lacked understanding of regulations and the technical skills required to use the SPSE system. The study highlights the need for training, regulatory literacy, and technical assistance, particularly in underdeveloped regions. These findings serve as a basis for local governments in designing more effective support policies for local contractors, contributing to broader digital transformation efforts in public procurement.